Lunar South Pole space water extraction and trucking system - Zuppero, A.; Zupp, G.; Schnitzler, B.; Larson, T. K.; Rice, J. W. (Idaho National Engineering and Environmental Laboratory, 1998)
This concept proposes to use thermal processes alone to extract water from the lunar South Pole and launch payloads to low lunar orbit. Thermal steam rockets would use water propellant for space transportation. The estimated mass of a space water tanker powered by a nuclear heated steam rocket suggests it can be designed for launch in the Space Shuttle bay. The performance depends on the feasibility of a nuclear reactor rocket engine producing steam at 1,100 degrees Kelvin, with a power density of 150 Megawatts per ton of rocket, and operating for thousands of 20 minute cycles. An example uses reject heat from a small nuclear electric power supply to melt 17,800 tons per year of lunar ice. A nuclear heated steam rocket would use the propellant water to launch and deliver 3,800 tons of water per year to a 100 km low lunar orbit.